2021
DOI: 10.1038/s41598-021-91758-3
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance is linked to a specific profile of immune activation in human subjects

Abstract: We tested the hypothesis that a particular immune activation profile might be correlated with insulin resistance in a general population. By measuring 43 markers of immune, endothelial, and coagulation activation, we have previously shown that five different immune activation profiles may be distinguished in 150 volunteers. One of these profiles, Profile 2, characterized by CD4+ T cell senescence, inflammation, monocyte, B cell, and endothelial activation, presented elevated insulinemia, glycemia, triglyceride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Our work unveils an immune activation signature linked to HIV-associated pre-frailty. It would now be of interest to perform the same kind of study in a non-specific population to test whether a similar signature is generally present in frailty, as we have shown that this is the case with insulin resistance [ 30 , 45 ]. In addition to its pathophysiological interest, the present study may have an implication for the management of frailty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work unveils an immune activation signature linked to HIV-associated pre-frailty. It would now be of interest to perform the same kind of study in a non-specific population to test whether a similar signature is generally present in frailty, as we have shown that this is the case with insulin resistance [ 30 , 45 ]. In addition to its pathophysiological interest, the present study may have an implication for the management of frailty.…”
Section: Discussionmentioning
confidence: 99%
“…We then generated a heatmap using the classification of patients and markers. For the supervised analysis, a linear discriminant analysis was applied to each solution (immunological marker combinations) using the R package MASS [ 30 ]. This supervised method creates linear combinations of all variables in order to optimize the separation of known classes.…”
Section: Methodsmentioning
confidence: 99%
“…As previously described (36,(39)(40)(41)(42), we then performed a double hierarchical clustering analysis again, using the following activation markers: sCD163, sTNFRI, tPA, sEPCR, the percentage of activated (CD38+, CD38hi, and/or HLA-DR+), exhausted (PD-1+), senescent (CD57+, eventually CD27-and eventually CD28-), naïve (CD45RA+CD27+), central (CD45RA-CD27+) and effector (CD45RA-CD27-) memory CD4+ and CD8+ T cells, as well as activated (HLA-DR+), dysfunctional (CD56-), and senescent (CD57+) NK cells. Percentages were preferred to absolute numbers as these are more stable over time.…”
Section: Identification Of Immune Activation Profiles Presented By 24...mentioning
confidence: 99%